Quantitative Aspects of Ruminant Digestion and Metabolism 2005
DOI: 10.1079/9780851998145.0049
|View full text |Cite
|
Sign up to set email alerts
|

Digesta flow.

Abstract: Using faecal instead of ruminal inoculum El Shaer et al. (1987); Omed et al. (2000) 2. Using cell-free enzymes. Cellulase Jones and Theodorou (2000). Acid pepsin þ cellulase Jones and Hayward (1975). Amylase þ cellulase Dowman and Collins (1982). Neutral detergent extraction þ cellulase Roughan and Holland (1977). Acid þ cellulase De Boever et al. (1988) 3. Solubility. Neutral detergent extraction Van Soest et al. (1991) In Vitro and In Situ Techniques for Estimating Digestibility 89

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…First, the greater food intakes of the free‐living koalas mentioned above and second, limitations of the particle‐associated marker Ru‐P used by Cork & Warner (1983). Adsorption of Ru‐P to the surface of particles is not irreversible, and thus the marker is in equilibrium with available binding sites in the digesta particle pool; this favours net movement of Ru‐P from larger to smaller particles because of their relatively larger surface areas (Faichney & Griffiths 1978; Faichney 2005). Cork & Warner (1983) reported that, in vitro , within 3 h of preparing large particles marked with Ru‐P, the Ru‐P was largely associated with particles that passed through a 109 µm mesh screen, and almost exclusively so after 24 h. Thus although their estimate of particle MRT may be based on some large particles cleared rapidly from the gut it is likely to be based predominantly on small particles selectively retained in the hindgut (Cork & Warner 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the greater food intakes of the free‐living koalas mentioned above and second, limitations of the particle‐associated marker Ru‐P used by Cork & Warner (1983). Adsorption of Ru‐P to the surface of particles is not irreversible, and thus the marker is in equilibrium with available binding sites in the digesta particle pool; this favours net movement of Ru‐P from larger to smaller particles because of their relatively larger surface areas (Faichney & Griffiths 1978; Faichney 2005). Cork & Warner (1983) reported that, in vitro , within 3 h of preparing large particles marked with Ru‐P, the Ru‐P was largely associated with particles that passed through a 109 µm mesh screen, and almost exclusively so after 24 h. Thus although their estimate of particle MRT may be based on some large particles cleared rapidly from the gut it is likely to be based predominantly on small particles selectively retained in the hindgut (Cork & Warner 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the influence of the gastric component is likely to be insignificant relative to the hindgut, and the first‐order kinetic model should provide realistic estimates of whole‐tract MRT. Faichney (2005) provides an alternative, non‐compartmental model for calculation of MRT from marker concentrations without complete collection of faeces. That model requires that all sampling periods be represented and collection be extended until levels reach background.…”
Section: Discussionmentioning
confidence: 99%
“…The survival times for DNA in silage and maize grain in the rumen are summarised in Table 1. Neither maize grain nor silage was detected in faecal material and DNA prepared from faeces did not contain amplifiable plant DNA target sequences. Rate of passage of digesta is slow in ruminants, but the last sample of faeces was collected 72 h after initial feeding of the test material and, with a daily intake of about 1000 g DM/d it is clear that plenty of opportunity was given for test food to have passed completely through the digestive tract (Faichney, 1993). Considering that only the smaller transgene sequence was detected in rumen samples collected after 24 h, the possibility of biologically significant DNA sequences in material passing through the sheep intestine, however, seems extremely low.…”
Section: Resultsmentioning
confidence: 99%
“…The mean retention time (MRT) of digesta in the terminal ileum and in the whole digestive tract was calculated from the concentration of solute (Co) and particle markers (Yb) in the digesta and faeces according to Faichney (1993) as follows:…”
Section: Calculations and Statistical Methodsmentioning
confidence: 99%